Serological detection of brucellosis among febrile, malaria-negative children and domesticated dogs in an urban African setting - John B. Kalule; Joseph Tomusange; Teddy Namatovu (AOSIS, 2020)
Background: Childhood brucellosis and malaria are co-endemic febrile illnesses in some sub-Saharan African countries. Malaria and brucellosis co-infection or brucellosis sole infections are often missed due to an over emphasis on malaria and the lack of appropriate diagnostic infrastructure. Brucellosis in dogs is usually overlooked and yet there is extensive contact between humans and their pets. Objective: This study investigated brucellosis in children and dogs using a confirmatory serological testing series that screens for three Brucella sp. Methods: Residual blood samples from malaria smear-negative febrile children were collected and tested for Brucella sp and malaria parasite. During the same period, residual blood samples presented to a veterinary microbiology laboratory in the same area were tested for brucellosis using the same approach. Results: A total of 105 human and 80 canine blood samples were tested for brucellosis antibodies. The seroprevalence of brucellosis was 22.86% (25/105) in children and 1.3% (1/80) in dogs using the Card, buffered acidified plate antigen, and standard plate agglutination tests but was 0% using the rivanol precipitation plate agglutination test. Conclusion: Given that brucellosis can be caused by both smooth and rough colony strains, there is a need to modify the current serological surveillance strategy (targeted at only Brucella abortus and other smooth colony Brucella strains) to figure out the relative contribution of rough colony Brucella strains (B. ovis and B. canis). Since Uganda is endemic for brucellosis there is a need to modify the brucellosis surveillance strategy.